5x+7(7x+11)=-193

Simple and best practice solution for 5x+7(7x+11)=-193 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+7(7x+11)=-193 equation:



5x+7(7x+11)=-193
We move all terms to the left:
5x+7(7x+11)-(-193)=0
We add all the numbers together, and all the variables
5x+7(7x+11)+193=0
We multiply parentheses
5x+49x+77+193=0
We add all the numbers together, and all the variables
54x+270=0
We move all terms containing x to the left, all other terms to the right
54x=-270
x=-270/54
x=-5

See similar equations:

| 60+7x=-10 | | 7g-3=11 | | 8x+58=5x+5 | | 8x+10+13x-5=180 | | -5(3x-13)=2(x-1)-35 | | 1+3n-5=-19 | | 5=6x=2x-7 | | 22x+4–9(2x)=0 | | 6^3t-1=36^t-3 | | 8.5g=340 | | 3x-8+4x=-36 | | 6-6=5x+30 | | 6x+2+62+74=180 | | (11x-4)=117 | | 21b+35=–3b+745.4 | | 9+5x=3(-x+3)-16 | | 4(2g-2)-10=g+17 | | 9x-9=117 | | t÷4-7=15 | | y2-6y+4y+156=180 | | 6x+2+62+74=90 | | 2+2j=-8 | | x=-3+-3 | | −2x+4=−12. | | 4x+8+x+1=2x-3+3x+4 | | 20+0.25x=10+0.75x | | (t-(1)/(6))^(2)=-(17)/(36) | | 8r-6=r+1 | | 25=4a-3 | | -2(5a+5)=18-6a | | 360=112+(80-3x)+(-9x+8)+(-5x+7) | | –5+5n=10n |

Equations solver categories